Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1526-4637.2012.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Volume of Local Anesthetic Required for an Ultrasound-Guided SGB

Abstract: In conclusion, when performing an ultrasound-guided SGB, 2 mL dosage was sufficient for a successful block as the previous, conventional volume. Therefore, when performing an ultrasound-guided SGB, we recommend the 2 mL dosage of local anesthetics for a successful block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…12 Ultrasound guidance could improve the accuracy of local anesthetic injection into target site. 15,16 The use of ultrasound-guided in the index case it apparently helpful in achieving therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Ultrasound guidance could improve the accuracy of local anesthetic injection into target site. 15,16 The use of ultrasound-guided in the index case it apparently helpful in achieving therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 2-mL 2% lidocaine was injected between the internal carotid artery and the longus colli at the C7 level under ultrasound guidance ( Figure 2). 15,16 The block was repeated once every day, and the pain subsided rapidly in both intensity and frequency along with the advancement of daily treatment. On the seventh day after treatment initiation, the patient no longer had pain episode.…”
Section: Case Presentationmentioning
confidence: 99%
“…They demonstrated how ultrasound-guided C6-SGB is performed beneath the prevertebral fascia in the longus colli muscle. Another study reported that a 2 mL dose is sufficient for a successful block when performing an ultrasound-guided SGB 12. Following the report of Narouze et al,13 we typically use 5 mL of the local anesthetic for ultrasound-guided SGB.…”
Section: Discussionmentioning
confidence: 96%
“…Kapral et al [ 7 ] and Narouze et al [ 13 ] reported a successful treatment effect with 5 mL of local anaesthetic in ultrasound-guided SGB. Two studies reported on the optimal volume of local anaesthetic required for successful ultrasound-guided SGB compared to the traditional approach [ 14 , 15 ]. One study showed that 4 ml of 0.2% ropivacaine was sufficient for a successful block [ 14 ], while the other showed the optimal volume was 2 ml of 0.5% mepivacaine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%